Outcome of Transsphenoidal Surgery for Cushing Disease: A Single-Center Experience Over 32 Years. Issue 2 (February 2016) - Chandler, William F.; Barkan, Ariel L.; Hollon, Todd; Sakharova, Alla; Sack, Jayson; Brahma, Barunashish; Schteingart, David E.
Abstract : BACKGROUND: Transsphenoidal surgery is the standard approach for treating Cushing disease. Evidence is needed to document effectiveness. OBJECTIVE: To analyze results of transsphenoidal surgery in 276 consecutive patients, including 19 children. METHODS: Medical records were reviewed for patients treated initially with surgery for Cushing disease from 1980 to 2012. Radiographic features, pathology, remissions, recurrences, and complications were recorded. Patients were categorized for statistical analysis based on tumor size (microadenomas, macroadenomas, and negative imaging) and remission type (type 1 = morning cortisol ⩽3 μg/dL; type 2 = morning cortisol normal). RESULTS: Females comprised 78% of patients and were older than men. Imaging showed 50% microadenomas, 13% macroadenomas, and 37% negative for tumor. Remission rates for microadenomas, macroadenomas, and negative imaging were 89%, 66%, and 71%, respectively. Patients with microadenomas were more likely to have type 1 remission. Pathology showed adrenocorticotropic hormone-secreting adenomas in 82% of microadenomas, in 100% of macroadenomas, and in 43% of negative imaging. The incidence of hyperplasia was 8%. The finding of hyperplasia or no tumor on pathology predicted treatment failure. The recurrence rate was 17%, with an average time to recurrence of 4.0 years. Patients with type 1 remission had a lower rate of recurrence (13% type 1 vs 50% type 2) and a longer time to recurrence. Children had similar imaging findings, remission rates, and pathology. There were no operative deaths. CONCLUSION: Transsphenoidal surgery provides a safe and effective treatment for Cushing disease. For both adults and children, the best outcomes occurred in patients with microadenomas and/or those with type 1 remission. ABBREVIATIONS: ACTH, adrenocorticotropic hormone IPSS, inferior petrosal sinus sampling